Designing Arabic Reading Instructional Materials Based on Qutrub’s Linguistic Triangles for University Students - Afrian, Zul; Haniah, Haniah; Waemamah, A-eshah (Borneo Journal of Language and Education, 2026)
This study examines the design of Arabic instructional materials intended to improve university students’ reading skills, especially in reading unvowelled Arabic texts, through the use of Qutrub’s linguistic triangles. The study addresses three main questions: how Qutrub’s linguistic triangles can support the development of Arabic reading skills, what form of instructional materials can be designed on the basis of these triangles, and how such materials may be pedagogically implemented in higher education. This research employed a qualitative library research design with a descriptive-analytic approach. Data were collected from Qutrub’s al-Muthallathat, its commentaries, classical and modern lexicons, and relevant studies on Arabic reading pedagogy and instructional-material development. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion drawing. The findings show that linguistic triangles provide not only lexical enrichment but also phonological, morphological, and semantic discrimination that can help learners distinguish visually similar lexical items in unvowelled texts. Based on the analysis, the study proposes instructional materials organized into vocabulary presentation, contextualized dialogues, guided reading texts, sentence-pattern exercises, and comprehension tasks. The study argues that Qutrub’s linguistic triangles may serve as a linguistically grounded resource for developing Arabic reading materials for non-native learners at the university level. The novelty of this study lies in integrating the classical Arabic lexical heritage of al-muthallathat into the contemporary design of Arabic reading instructional materials.